KEMENUH BUTTERFLY PARK EDU-TOURISM IN KEMENUH VILLAGE - GIANYAR - Anak Agung Ari Sutraningsih (UHN IGB Sugriwa Denpasar, 2023)
Diverse educational tourism has transformed the concept of tourism itself. The primary goal of educational tourism is to acquire knowledge and experience about specific subjects or research. Kemenuh Butterfly Park is one concept of educational tourism that emphasizes conservation and education in the Gianyar, Bali region. This research aims to discuss the educational tourism model at Kemenuh Butterfly Park. Using a qualitative descriptive model, the study seeks to understand the general overview of educational tourism applied and offered in the concept of sustainable tourism. Literature review is conducted to support this research. The results of the research indicate that the educational concept has a limitation concerning its targeted tourist segment. Additionally, educational tourism concepts are still rarely included in existing tour packages. In the alternative tourism model, it is hoped that educational tourism will not be just a temporary trend but can evolve into sustainable tourism